Peri-mortem disease treatment: a little known cause of error in the estimation of the time since death in decomposing human remains. Issue 2 (3rd March 2016) - Hayman, Jarvis; Oxenham, Marc
Abstract : As part of a larger study into the estimation of the time since death of human bodies found decomposed, two bodies were monitored closely while decomposing in sequence in almost identical environmental situations. Both the rate and the manner, or stages, of decomposition that occurred to each body varied greatly and it is suggested that this was due to peri-mortem disease treatment of one of the bodies immediately prior to death. The results of this study suggest that certain forms of peri-mortem disease treatment are more important in modifying the process of post-mortem decomposition than previously thought to be case. In particular, cytotoxic drugs and/or antibiotic drug treatments in the peri-mortem period may contribute to altered rates and patterns of decomposition that have the potential to affect the estimation of the time since death in human bodies found decomposed.